2001
DOI: 10.1007/s002130100834
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment inhibits protein kinase C translocation in rat brain cortex

Abstract: Lithium treatment reduces PKC translocation induced by either stimulation of a cell surface receptor or by direct enzyme stimulation with phorbol ester. This effect leads to reduced PKC-mediated phosphorylation of cellular proteins and may be responsible for the pharmacotherapeutic action of lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 2 publications
3
30
1
Order By: Relevance
“…This absence of change in total PKC activity was ascribed to a high abundance of PKC g, a neuron-specific PKC, which is the major contributor to total PKC activity, thus masking changes in activities of the other PKC isoforms (Wang et al, 2001). The lack of effect on basal activity by lithium that we observed in this study may be due to the contribution of activity by other PKC isoforms, which masked the changes in the PKC a and PKC e activities.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…This absence of change in total PKC activity was ascribed to a high abundance of PKC g, a neuron-specific PKC, which is the major contributor to total PKC activity, thus masking changes in activities of the other PKC isoforms (Wang et al, 2001). The lack of effect on basal activity by lithium that we observed in this study may be due to the contribution of activity by other PKC isoforms, which masked the changes in the PKC a and PKC e activities.…”
Section: Discussioncontrasting
confidence: 43%
“…Earlier studies indicated that chronic lithium treatment altered PKC isoforms in rat frontal cortex, without changing total tissue PKC activity (Wang et al, 2001). This absence of change in total PKC activity was ascribed to a high abundance of PKC g, a neuron-specific PKC, which is the major contributor to total PKC activity, thus masking changes in activities of the other PKC isoforms (Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…98 PKC activation requires translocation to the membrane where it interacts with the receptor for activated C-kinase-1 (RACKS-1) protein. Li þ treatment reduces this translocation, consistent with reduced generation of DAG from PdtIns(4,5)P 2 , 99 and increased association with RACK-1 has been observed in post-mortem brains from bipolar patients. 100 Chronic Li þ treatment in rats decreases both PKC activity and phosphorylation of a PKC substrate, myristoylated alanine-rich C kinase substrate (MARCKS), 101 an effect reversed by addition of myoinositol.…”
Section: Calcium Signalingsupporting
confidence: 73%
“…The chronic LiCl diet of this study is reported to reduce global brain mRNA, protein and activity levels of cPLA 2 in rats, but not to affect expression of sPLA 2 or iPLA 2 (Bosetti et al, 2002a, b;Chang and Jones, 1998;Rapoport and Bosetti, 2002;Rintala et al, 1999;Weerasinghe et al, 2004). Its cPLA 2 effect may be due a lithium-induced downregulation of Ca 2 + -dependent PKC, to reduce expression of PKC-dependent AP-2, which regulates cPLA 2 transcription (Rao et al, 2005;Wang et al, 2001). Consistent with selective cPLA 2 targeting, the LiCl diet reduces incorporation and turnover rates of AA but not of DHA in brain phospholipids of unanesthetized rats (Chang et al, 1996).…”
Section: Discussionmentioning
confidence: 65%